1980
DOI: 10.1159/000119917
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Aneurysms of Childhood

Abstract: 15 cases of cerebral aneurysms in children between 8 and 15 years of age, all operated upon in a 20-year span (1956–1976), are reported. 7 of them were the carriers of large aneurysms (3 ‘giant’). Surgical mortality was limited to 2 patients with aneurysms of the middle cerebral artery and large intracerebral hematomas. All other patients are in satisfactory conditions, with a follow-up ranging from 2 to 22 years. A direct approach to the aneurysm was used in all but 3 cases. Certain features of cerebral aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
58
0
5

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 6 publications
5
58
0
5
Order By: Relevance
“…Os aneurismas em crianças menores de cinco anos, como ocorrido em nosso paciente, são considerados raros e correspondem a menos de 0,1% de todos os aneurismas diagnosticados, sendo mais freqüentes nos dois primeiros anos de vida 5 -1 2 . Existe predomínio do sexo masculino na infância 2-2,8/1, ao contrário do predomínio no sexo feminino observado na idade adulta 1,3,5,7,13 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Os aneurismas em crianças menores de cinco anos, como ocorrido em nosso paciente, são considerados raros e correspondem a menos de 0,1% de todos os aneurismas diagnosticados, sendo mais freqüentes nos dois primeiros anos de vida 5 -1 2 . Existe predomínio do sexo masculino na infância 2-2,8/1, ao contrário do predomínio no sexo feminino observado na idade adulta 1,3,5,7,13 .…”
Section: Discussionunclassified
“…Menos de 5% dos aneurismas nesta faixa etária são diagnosticados antes dos cinco anos de idade [1][2][3][4] . Apesar da pequena incidência, ressalta-se a gravidade da doença devido a grande ocorrência de ru p t u r a , sendo a principal causa de hemorragia subaracnóidea na infância, 40-52,1% 1,[5][6][7] .…”
unclassified
See 1 more Smart Citation
“…5,7,19,21,24,28,32 Aneurysms in the first 2 decades of life account for 1%-4% of all intracranial aneurysms. 12,15,17,29 As in adults, the treatment of intracranial aneurysms in children can involve microsurgical clip ligation, wrapping, and endovascular treatment including flow diversion, coiling, and embolization of the aneurysm and parent vessel.…”
mentioning
confidence: 99%
“…It was demonstrated that large stress from the pulsating blood pre ssure produced structural fatigue in the arterial wall and degenerated the internal elastic lamina 2 5 . The role of hemodynamic factors is clearly illustrated by the preponderance of ICA bifurcation aneurysms is 24 to 50% and only 2.1% in adults 3,6,13 .…”
mentioning
confidence: 99%